Domača tujost antičnih imen in "Zakon o javni rabi slovenščine" - Sunčič, Maja (Keria (Ljubljana), 2004)
The paper discusses the alien or familiar quality of ancient names in the naming of Slovenian enterprises in view of the Law of the Public Use of Slovene (LPUS) and a detailed study of Alenka Gložančev. The issue of the public use of ancient names is largely ignored by the LPUS and the language-conscious public, except in the cases when foreign-language use reaches an extreme level. The question arises why ancient names are not defined as problematic despite being at least as unclear and non-Slovene as, for example, English ones. Can it be expected that, in the name of defending the Slovene language and cultural heritage, the restrictions enforced by LPUS on the use of foreign names will contribute to the disappearance of antiquity from contemporary everyday life?
Keywords: antična imena; grška imena; javna raba; latinska imena; onomastika; slovenščina; Zakon o javni rabi slovenščine